Carbon Dioxide and Methane Emissions from Eutrophic, Vegetated Coastal Lagoons Potentially Offset Carbon Accumulation in Eelgrass Sediments - C. Wigand; S. Ayvazian; N. Bartolucci; A. Beardwood; S. Miller; D. Cobb; P. Colarusso; N. Merrill; K. Miller (Estuaries and Coasts, 2026)

Higher alkalinity increases copper toxicity in phytoplankton: The importance of pH flux when treating algal blooms - Anna C. Mollica; Megan T. Wesche; Matthew F. Gladfelter; Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Kate L. Merrill; Alan E. Wilson (Harmful Algae, 2026)

Repeated low-dose copper algaecide treatments promote beneficial phytoplankton and zooplankton communities - Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Journal of Environmental Management, 2025)

Evaluating the tolerance of harmful algal bloom communities to copper - Ashley V. Hennessey; Michael B. McDonald; Peyton P. Johnson; Matthew F. Gladfelter; Kate L. Merrill; Suzanne E. Tenison; Sathya S. Ganegoda; Tham C. Hoang; H. Allen Torbert; Benjamin H. Beck; Alan E. Wilson (Environmental Pollution, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Ecological Interactions Between Non-Native American Shad and Pacific Salmon: The Columbia River Case Study - Thomas P. Quinn; John Epifanio; Peter B. Moyle; Stan Gregory; Daniel J. Hasselman; Erik Merrill; Kenneth Rose; Thomas F. Turner; Thomas C. Wainwright (Reviews in Fisheries Science & Aquaculture, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers and dysregulation of MicroRNA expression in humans and animals—A systematic review - Yijie Li; Brittney O. Baumert; Elizabeth Costello; Jiawen Carmen Chen; Sarah Rock; Nikos Stratakis; Jesse A. Goodrich; Yinqi Zhao; Sandrah P. Eckel; Douglas I. Walker; Damaskini Valvi; Michele A. La Merrill; et al. (Environmental Research, 2024)

The contributions of neonatal inhalation of copper to air pollution-induced neurodevelopmental outcomes in mice - Janine Cubello; Elena Marvin; Katherine Conrad; Alyssa K. Merrill; Jithin V. George; Kevin Welle; Brian P. Jackson; David Chalupa; Günter Oberdörster; Marissa Sobolewski; Deborah A. Cory-Slechta (NeuroToxicology, 2024)

Microplastics in marine mammal blubber, melon, & other tissues: Evidence of translocation - Greg B. Merrill; Ludovic Hermabessiere; Chelsea M. Rochman; Douglas P. Nowacek (Environmental Pollution, 2023)

Correction to: Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown‑Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2023)

Networks of placental DNA methylation correlate with maternal serum PCB concentrations and child neurodevelopment - Julia S. Mouat; Xueshu Li; Kari Neier; Yihui Zhu; Charles E. Mordaunt; Michele A. La Merrill; Hans-Joachim Lehmler; Michael P. Jones; Pamela J. Lein; Rebecca J. Schmidt; Janine M. LaSalle (Environmental Research, 2023)

Mapping of a novel major effect Hessian fly field partial-resistance locus in southern soft red winter wheat line LA03136E71 - Z. J. Winn; R. Acharya; K. Merrill; J. Lyerly; G. Brown-Guedira; S. Cambron; S. H. Harrison; D. Reisig; J. P. Murphy (Theoretical and Applied Genetics, 2021)

Waiting and “weighted down”: the challenge of anticipatory loss for individuals and families with Li-Fraumeni Syndrome - Allison Werner-Lin; Jennifer L. Young; Catherine Wilsnack; Shana L. Merrill; Victoria Groner; Mark H. Greene; Payal P. Khincha (Familial Cancer, 2020)

Development and Validation of Technologies for Remediation of 1,2,3-Trichloropropane in Groundwater - John P. Merrill; Eric J. Suchomel; Srinivasa Varadhan; Melissa Asher; Lea Z. Kane; Elisabeth L. Hawley; Rula A. Deeb (Current Pollution Reports, 2019)

Trade‐offs for data‐limited fisheries when using harvest strategies based on catch‐only models - Jessica C. Walsh; Cóilín Minto; Ernesto Jardim; Sean C. Anderson; Olaf P. Jensen; Jamie Afflerbach; Mark Dickey‐Collas; Kristin M. Kleisner; Catherine Longo; Giacomo Chato Osio; Elizabeth R. Selig; James T. Thorson; et al. (Fish and Fisheries, 2018)
Many of the world's fisheries are unassessed, with little information about population status or risk of overfishing. Unassessed fisheries are particularly predominant in developing countries and in small‐scale fisheries, where they are important for food security. Several catch‐only methods based on time series of fishery catch and commonly available life‐history traits have been developed to estimate stock status (defined as biomass relative to biomass at maximum sustainable yield: B/ B MSY ). While their stock status performance has been extensively studied, performance of catch‐only models as a management tool is unknown. We evaluated the extent to which a superensemble of three prominent catch‐only models can provide a reliable basis for fisheries management and how performance compares across management strategies that control catch or fishing effort. We used a management strategy evaluation framework to determine whether a superensemble of catch‐only models can reliably inform harvest control rules ( HCR s). Across five simulated fish life histories and two harvest‐dynamic types, catch‐only models and HCR combinations reduced the risk of overfishing and increased the proportion of stocks above B MSY compared to business as usual, though often resulted in poor yields. Precautionary HCR s based on fishing effort were robust and insensitive to error in catch‐only models, while catch‐based HCR s caused high probabilities of overfishing and more overfished populations. Catch‐only methods tended to overestimate B/ B MSY for our simulated data sets. The catch‐only superensemble combined with precautionary effort‐based HCR s could be part of a stepping stone approach for managing some data‐limited stocks while working towards more data‐moderate assessment methods.

Hierarchical trade-offs between risk and reward mediated by behavior - D. R. Visscher; E. H. Merrill; P. K. Martin (Mammal Research, 2017)

Application of a single-objective, hybrid genetic algorithm approach to pharmacokinetic model building - Eric A. Sherer; Mark E. Sale; Bruce G. Pollock; Chandra P. Belani; Merrill J. Egorin; Percy S. Ivy; Jeffrey A. Lieberman; Stephen B. Manuck; Stephen R. Marder; Matthew F. Muldoon; Howard I. Scher; David B. Solit; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Spatial and non‐spatial risk factors associated with cage‐level distribution of infectious salmon anaemia at three Atlantic salmon, Salmo salar L., farms in Maine, USA - L Gustafson; S Ellis; T Robinson; F Marenghi; P Merrill; L Hawkins; C Giray; B Wagner (Journal of Fish Diseases, 2007)
The distribution of infectious salmon anaemia (ISA) was examined among 80 cages from three Atlantic salmon grow‐out farms in Maine, USA that were stocked with smolts from a single hatchery. Cage‐level disease was broadly defined as one or more moribund fish testing positive for infectious salmon anaemia virus (ISAV) by RT‐PCR and a second confirmatory test (IFAT, culture or genotype sequence). Spatio‐temporal and cage‐level risks were explored using logistic regression and survival analysis. Non‐spatial risk factors associated with ISA, or shortened survival time to disease, included increased predation, trucking company choice for smolt transfers, a finely‐sedimented benthic substrate, and smaller average size of smolts at stocking. Univariable analysis identified the time‐dependent spatial factor ‘adjacency to newly infected cages’ to be predictive of new infection in neighbouring cages 11–12 weeks later. However, none of the spatial factors, or their lags retained relevance in multiple‐variable models. The results suggest a diffuse distribution of virus exposure throughout infected sites, with host‐susceptibility factors probably influencing disease manifestation in individual cages. The narrow focus of the current study may limit application of the findings to other sites and year‐classes. However, these data support the relevance of husbandry efforts to optimize fish health in regions affected by ISAV.

Letters - T. La Farge; J. Merrill; G.L. Price; P. Buist; S. Pennington (Journal of Forestry, 2001)

Regulation of gene expression in the nervous system by reactive oxygen and nitrogen species - Jean E. Merrill; Sean P. Murphy (Metabolic Brain Disease, 1997)

A knowledge-based expert system for planning and design of agroforestry systems - Merrill E. Warkentin; P. K. R. Nair; Stephen R. Ruth; Kristopher Sprague (Agroforestry Systems, 1990)